Management of the Orally Compromised Medical Patient - Juan Yepes (Association of American Medical Colleges, 2012)
Abstract This resource is designed to provide dentist, physicians, and students with a basic understanding of how various medical disorders can affect oral health (or dental disorders affect the systemic health) and the delivery of dental and medical care. This course is different from most other dental courses involving medically compromised patients in that it requires the participant to assess each patient individually and determine the severity of their medical condition, the level of control and risk for care, and need for treatment modifications. The participant will learn the process of medical risk assessment and treatment planning for patients with various medical disorders. Emphasis is placed upon evidence-based recommendations, researching and using various information resources and participating in case discussions. This course was designed using the framework developed at the University of Kentucky. The intent was to bring orally-compromised patients to medicine, a twist of the traditional course of dental management of the medically compromised patient. Cases of patients orally compromised (e.g., with gingivitis, caries, migratory glossitis, candidiasis, etc.) will be presented to medical students and physicians. Each case will have a history, pictures, implications for the systemic health, and treatment. The key to successful medical management of orally compromised patients is thorough evaluation and assessment of the oral condition to determine the future treatment. Using real cases with orally compromised patients, medical students and physicians will see and evaluate the consequences of the oral health in the systemic health from a different optic. The work is the end result of more than 15 years of teaching medically compromised patients to dental students.